A Strongly Fluorescent Dye Featuring a Multiple N-doped Polycyclic Aromatic Hydrocarbon Skeleton - Chen, Peihao; Wan, Xintong; Zhang, Yi; Chang, Xiaoyong; Ouyang, Ping; Xiong, Jinfan; Zou, Yang; Liu, He; Cheng, Gang; Li, Kai (Synlett, 2025)
This study presents the synthesis and characterization of a highly fluorescent compound derived from 5,11-dihydroquinoxalino[2,3-b]quinoxaline (tBQQ), which incorporates both sp3 and sp2 nitrogen atoms into a polycyclic aromatic hydrocarbon skeleton. Starting from 3,6-di-tert-butyl-9H-carbazole, the target compound was obtained in moderate yield through a key condensation cyclization and subsequent oxidation reactions. The new compound exhibits excellent photophysical properties, including intense absorption and high photoluminescence quantum yield (96%). Taking together the electrochemical and computational studies, its bipolar nature is suggested. The fluorescence sensing capability toward acid was also revealed for tBQQ, attributable to the presence of sp2 N atoms. This study provides an unexplored skeleton for the design of strongly fluorescent dyes toward various applications.
Keywords: Fluorescence; N-Heterocycles; π-Conjugated system; Polycyclic aromatic hydrocarbon; Organic semiconductor